Negative Impact of Comorbidity on Health-Related Quality of Life Among Patients With Stroke as Modified by Good Diet Quality - Pham, Thu T. M.; Vu, Manh-Tan; Luong, Thuc C.; Pham, Khue M.; Nguyen, Lien T. K.; Nguyen, Minh H.; Do, Binh N.; Nguyen, Hoang C.; Tran, Tuan V.; Nguyen, Thao T. P.; Le, Hoang P.; Tran, Cuong Q.; et al. (Frontiers in Medicine, 2022)
Background: Comorbidity, along with aging, affect stroke-induced health-related quality of life (HRQoL). We examined the potential role of diet quality in modifying the association between comorbidity and HRQoL in stroke patients. Methods: A cross-sectional study was conducted on 951 stroke patients from December 2019 to December 2020 across Vietnam. Comorbidity was assessed using the Charlson Comorbidity Index items and classified into two groups (none vs. one or more). Diet quality was evaluated using the Dietary Approaches to Stop Hypertension Quality (DASH-Q) questionnaire, and HRQoL was measured using the RAND-36, with a higher score indicating better diet quality or HRQoL, respectively. Besides, socio-demographics, health-related behaviors (e.g., physical activity, smoking, drinking), disability (using WHODAS 2.0), and health literacy were also assessed. Linear regression analysis was utilized to explore the associations and interactions. Results: The proportion of stroke patients aged ≥ 65 years and having comorbidity were 53.7% and 49.9%, respectively. The HRQoL scores were 44.4 ± 17.4. Diet quality was associated with higher HRQoL score (regression coefficient, B, 0.14; (95% confidence interval, 95% CI, 0.04, 0.23; p = 0.004), whereas comorbidity was associated with lower HRQoL score (B, -7.36; 95%CI, -9.50, -5.23; p < 0.001). In interaction analysis, compared to patients without comorbidity and having the lowest DASH-Q score, those with comorbidity and higher DASH-Q score had a higher HRQoL score (B, 0.21; 95%CI, 0.03, 0.39; p = 0.021). Conclusions: The findings showed that good diet quality could modify the adverse impact of comorbidity on HRQoL in stroke patients. Diet quality should be considered as a strategic intervention to improve stroke patients’ HRQoL, especially those with comorbidity, and to promote healthier aging.